Post-disaster social work research: A scoping review of the evidence for practice. (May 2022) - Harms, Louise; Boddy, Jennifer; Hickey, Lyndal; Hay, Kathryn; Alexander, Melinda; Briggs, Lynne; Cooper, Lesley; Alston, Margaret; Fronek, Patricia; Howard, Amanda; Adamson, Carole; Hazeleger, Tricia
The aim of this study was to understand the extent, range and nature of social work research activity after natural disasters and to identify the implications for future research and practice. A Scoping review methodology framework was used search of three databases: Web of Science, ProQuest and Informit was conducted to identify relevant studies between 2000 and 2018. Selection of studies was based on empirical research about social work and natural disasters and/or authored by social workers. Study selection found a total of 38 relevant articles. Charting the data was conducted and the following areas of focus were summarised: (1) interventions relating to psychosocial care, aid work and community work; (2) the effects of disasters on people and mediators of these effects; (3) social work education and challenges in disaster relief; and (4) measuring mental health outcomes of people who have experienced a disaster event. This scoping review has established that there is a range of social work literature focused on natural disasters that primarily examines social work interventions, the effects of disasters and social work education. Future social work research and practice needs to focus on the types and timing of interventions that promote positive recovery following natural disasters.